Wilson’s Disease; Clinical Presentations among Patients Attending Gastroenterology Clinic/ Baghdad Teaching Hospital - . Mohammed, Ahmed Kh; Najeeb, Akram Ajeel; Tawfeeq, Wafaa Faeq (AL-Kindy College Medical Journal, 2013)
Background:Wilson’s disease (WD) is an inherited disorder of copper metabolism that is characterized by tremendous variation in the clinical presentation. Objective: To assess demographic distribution, clinical presentations, diagnostic evaluation, and any association between clinical presentations and other studied variables of a sample of Iraqi patients with WD. Methods: A descriptive cross sectional study with analytic elements was conducted during 2011, from the 1st of February till the 10th of June. The sampling method was a convenient non-random one, carried out through consecutive pooling of registered WD patients. A questionnaire-form paper had been developed for the process of data collection. Results: The study had enrolled 29 patients, with a male to female ratio of (1.07:1), their mean age was 27.12±12.18 years. 82.8% of them lived in urban area. 48.3% were singles. Only 20.7% of patients had a positive family history of WD. 69% of patients had consanguineous parents. The main initial clinical presentations were; hepato-neurologic (31%), pure hepatic (27.6%), neuro-psychiatric (13.8%) and other presentations (27.6%). Hepatic manifestations were seen in (82.8%) of patients; jaundice was the most frequent (89.7%). Ophthalmologic manifestations in (55.1%) of patients including; Kayser-Fleischer rings (51.7%), diplopia (6.9%) and cataracts (3.4%). Neurologic manifestations existed in 44.8% of patients; tremors were the most frequent (41.4%). Psychiatric manifestations existed in 31% of patients; depression was the commonest (27.6%). Joints manifestations existed in 20.7% of patients. The diagnosis delay was 11.26±8.2 months. Conclusion: The higher percentage of patients were of hepato-neurologic and pure hepatic presentations. Patients with hepato-neurologic type are diagnosed in older age, while those with neuro-psychiatric type are diagnosed in younger age and with longer diagnosis delay.